Analysis of Quality Costs in Efforts to Improve the Financial Performance of the Company: An Empirical Study at CV Central Fragrance Utama - Sakeletuk, Regina; Sahroni, Sahroni; Marjohan, Masno (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze quality costs in relation to improving the financial performance of CV Central Fragrance Utama during the 2022-2024 period. Specifically, the research focuses on three aspects: (1) classification and measurement of quality costs, which include prevention, appraisal, internal failure, and external failure costs; (2) evaluation of financial performance based on profitability, liquidity, solvency, and activity ratios; and (3) analysis of the efficiency of quality cost management in supporting financial performance improvement. The research method uses a descriptive-qualitative approach with data collection techniques through observation, interviews, and document analysis. The results show that the allocation of quality costs is not yet optimal. Prevention costs decreased significantly from 78.12% to 48.82%, while internal and external failure costs increased. Financial performance shows sales growth that improves NPM and ROA, but ROE remains negative with critical liquidity and solvency conditions. The efficiency of quality costs has not been consistently achieved due to a decrease in investment in prevention and appraisal areas. The company needs to increase the proportion of prevention costs, strengthen its quality control system, and restructure capital to achieve healthy financial performance and sustainable growth.